Analisis Kelayakan Usaha Keripik Singkong di Desa Kemuning Lor Kecamatan Arjasa Kabupaten Jember - Zaini, Ahmad; Zuniana, Qory (KUBIS, 2024)
Kemuning Lor Village, Arjasa District, Jember Regency has potential in Mr. Jumairi's cassava chips business, but there are still problems in his cassava chips business, namely that it is not well managed so farmers don't know how much income their business will earn or don't even know whether their business is making a profit or a loss. The cassava chips business in Kemuning Lor Village actually has potential because the opportunities are still wide open considering the high demand for cassava chips and relatively stable selling prices. Therefore, the researcher wants to know whether Mr. Jumairi's cassava chips business in Kemuning Lor Village, Arjasa District, Jember Regency is profitable and feasible for the sampling method using purposive sampling because he deliberately took Mr. Jumairi's cassava chips business for reasons that met the specified criteria. by researchers and this research was carried out from November 2022 to July 2023. Based on the results of the analysis carried out, it shows that Mr. Jumairi's cassava chips business in Kemuning Lor Village is worth pursuing and the results of the sensitivity analysis show that this cassava chips business is not sensitive to changes in interest rates of 10% to 15%